Study and Analysis of Removing the Carbon Deposition on the Inner Surface of a Turbo-Shaft by Chemically Assisted Magnetic Grinding - Xu, Hui; Kang, Renke; Zhu, Xianglong; Liu, Lijuan; Wang, Leilei; Chen, Yan (Frontiers in Materials, 2020)
It has always been a tough problem to remove carbon deposition (CD). On the inner surface of a turbo-shaft, the CD is observed by Scanning Electron Microscope (SEM) to analyze its microstructure and composition, and its formation mechanism is analyzed by X-Ray Diffraction (XRD), Infrared Spectrum (IS) and Raman spectra. Considering the physical and chemical properties of the above CD, chemically assisted magnetic grinding (CAMG) is put forward with the result to be tested by a translational permanent magnet grinding device. By analyzing the removing mechanism of CAMG, response surface analysis is adopted to analyze the influence law on surface roughness by the interactions between every two of the three following parameters, rotational speed of rotating magnetic field, needle type and grinding time. The optimal process parameters can be obtained with the rotational speed of rotating magnetic field being 600 r/min, the needle type being Φ1.0 mm×5 mm, the grinding being time 60 min. The surface quality of the work piece processed by CAMG can be comprehensively appraised through observing the microstructure, calculating the CD removal ratio and testing the surface stress. Comparing to single magnetic grinding, CAMG is more environmental-friendly and has a higher removal ratio and a better surface quality with residual stress decreasing obviously. Through professional tests, the remaining CD is less than the specified value required by the technology, which meets enterprises’ requirements.